2017
DOI: 10.1038/s41598-017-05642-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms and Platinum-based Chemotherapy Treatment Outcomes in Patients with Non-Small Cell Lung Cancer: A Genetic Epidemiology Study Based Meta-analysis

Abstract: Data regarding genetic polymorphisms and platinum-based chemotherapy (PBC) treatment outcomes in patients with NSCLC are published at a growing pace, but the results are inconsistent. This meta-analysis integrated eligible candidate genes to better evaluate the pharmacogenetics of PBC in NSCLC patients. Relevant studies were retrieved from PubMed, Chinese National Knowledge Infrastructure and WANFANG databases. A total of 111 articles comprising 18,196 subjects were included for this study. The associations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
18
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 97 publications
8
18
2
1
Order By: Relevance
“…Other three meta‐analyses confirmed these observations in advanced NSCLC patients treated with platinum‐based chemotherapy. Tan et al found an association between the A allele of rs11615 ERCC1 gene and shorter OS . Similar effect was shown by Yang et al and Xu et al They shown shorter OS in patients with the A allele of rs11615 ERCC1 gene .…”
Section: Discussionsupporting
confidence: 56%
“…Other three meta‐analyses confirmed these observations in advanced NSCLC patients treated with platinum‐based chemotherapy. Tan et al found an association between the A allele of rs11615 ERCC1 gene and shorter OS . Similar effect was shown by Yang et al and Xu et al They shown shorter OS in patients with the A allele of rs11615 ERCC1 gene .…”
Section: Discussionsupporting
confidence: 56%
“…Since only a few studies in Caucasians were available, we gave up the subanalysis of Caucasians in the present study. Compared with previous meta-analyses 50 52 , we included more eligible studies and a larger sample size of more than 5500 patients under similar genetic background, indicating a stronger robustness of our results.…”
Section: Discussionmentioning
confidence: 94%
“…Thus, we conducted a retrospective cohort study to test whether SNPs in genes involved in the NER pathway are associated with prognosis in male patients with OSCC treated with adjuvant CCRT. A total of 13 SNPs in ERCC5 , ERCC2 , ERCC1 , XPC , and XPA genes, which have been found to affect the risk and/or survival of cancers, were selected in the present study [13,14,16,17,18,19,20]. Their associations with clinical outcomes were evaluated using alternative genetic models, including additive, dominant, and recessive models.…”
Section: Introductionmentioning
confidence: 99%